Critical Review: "DISABILITY, POVERTY, AND ROLE OF THE BASIC LIVELIHOOD SECURITY SYSTEM ON HEALTH SERVICES UTILIZATION AMONG THE ELDERLY IN SOUTH KOREA" - Rina Lusiana Handayanti, Rina (2021)
Tugas Mata Kuliah Kemiskinan